The Contrast Between Conventional and Formal Issues, in a Modernising Country - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Turkey, is undergoing a fast modernization process on one hand; but people still cling to traditional ways, on the other hand. This dual character makes it difficult for the formal and informal aspects of social life to go in parallel. There is a gap between anything officially on paper and the actual social reality of the real world out there. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Tradition; traditional; formal; informal, modern